A Nomenclator of Ficus sect. Americanae (Moraceae). Part I: South America - Mitidieri-Rivera, Nicole; Damián-Parizaca, Alexander; Gardner, Elliot M.; Plata-Castro, Angelo D.; Zerega, Nyree J.c.; Pederneiras, Leandro C. (Phytotaxa, 2025)
Continuous revisions in nomenclature are crucial for maximally informative and stable classification systems as well as accurate assessments of biodiversity. As a precursor to a phylogenetic-based, taxonomic monograph of Neotropical Ficus sect. Americanae (Moraceae), a comprehensive nomenclatural index of all published names in the section from South America is treated here. We reviewed the protologues, local and regional floras, and the type vouchers of each taxon described for F. sect. Americanae in the last four centuries. Application of the term holotype is corrected to lectotype for 37 names (ICN, Art. 9.12) and type is corrected to lectotype for five names (ICN, Art. 9.17). The term type is corrected to neotype for four names (i.e., Ficus diabolica fo. laurina, F. diabolica fo. major, F. diabolica fo. minor, and F. speciosa). The nomenclatural designations in this work will facilitate the accurate naming of clades identified in future integrated systematic studies of F. sect. Americanae, thereby clarifying the taxonomy of this section. This index serves as a critical reference for future taxonomic and systematic research on Ficus worldwide.